The role of teachers' resource centres from the perspective of school managers and teachers - Mbambo, Markus S (Rhodes University, Faculty of Education, Department of Education, 2010)
This study aimed to investigate the role played by the Teachers' Resource Centre (TRC) in Namibia in helping schools to provide quality education. The TRC concept began in Britain in the 1960s, where it was introduced as a means of supporting the professional development of teachers and giving them access to a range of educational resources. From the 1970s, the concept was promoted further afield as an effective strategy for dealing with teachers' needs. TRCs emerged in Namibia in the 1980s under the auspices of the then Department of Education of the South African government. By 1989, only four TRCs were in existence, namely, Katutura, Tsumeb, Otjiwarongo and Rundu, plus one in the whites-only training college in Windhoek. In September 1991, the Ministry of Education and Culture (MEC) in Namibia produced a five-year plan that led to the diversification of the TRC network in Namibia. Yet, despite the now widespread existence of TRCs, little is known of whether and to what extent their services are helping teachers to provide quality education. This constitutes a gap in the literature that this study hopes in part to fill. The study was conducted using a case study approach in three schools in the Kavango region of Namibia. It made use of questionnaires, interviews, focus group discussions and data analysis to gather and interpret data. The study's finding is that TRCs are indeed beneficial to schools in their vicinity, despite their current limited capacities. However, TRCs should be better able to redress the poor quality of education in many schools due to a lack of resources, de-motivated teachers and other factors. This study therefore recommends that enough funds be made available for the TRCs to acquire the resources they need adequately to support quality educational processes. Furthermore, the study found that it is imperative for individuals in TRCs and schools to learn how to facilitate relevant transformation in their organisations' efficiency and effectiveness. Thus the study recommends a transformational leadership approach as most appropriate for managing learning and bringing about successful change in these organisations. The significance of this research is that it sheds some light on the effectiveness of TRCs as a strategy for supporting teachers in the delivery of quality teaching. It also suggests potential areas in which stakeholders might usefully cooperate in their endeavours to realise quality education.
Keywords: Education -- Namibia; Teaching -- Aids and devices -- Namibia; Resource programs (Education) -- Namibia; Teachers -- Namibia -- Case studies